2001
DOI: 10.1016/s0006-3495(01)75983-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the pH-Denatured States of Ferricytochrome-c by Synchrotron Small Angle X-Ray Scattering

Abstract: The ferricytochrome-c (cyt-c) shows a complex unfolding pathway characterized by a series of stable partially folded states. When titrated with HCl at low ionic strength, two transitions are detected. At pH 2, cyt-c assumes the U1 unfolded state, whereas the successive addition of Cl(-) ion from either HCl or NaCl induces the recompaction to a molten globule conformation (A1 and A2 states, respectively). A second unfolded state (U2) is also observed at pH 12. Recent data evidence different features for the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 35 publications
7
44
0
Order By: Relevance
“…A significant increase in the percentage content of β-turn was observed in the spectrum of β-turn band and it exhibited 3cm -1 difference at 1685 cm -1 than that of the native state. This is in agreement with results reported by near UV CD (Goto et al, 1990;Qureshi et al, 2003), hydrogen exchange/2D NMR (Jeng et al, 1990), X-ray scattering (Cinelli et al, 2001). Conclusion: It has been observed that pH have affected ditrisbution of secondary structures.…”
Section: Resultssupporting
confidence: 92%
“…A significant increase in the percentage content of β-turn was observed in the spectrum of β-turn band and it exhibited 3cm -1 difference at 1685 cm -1 than that of the native state. This is in agreement with results reported by near UV CD (Goto et al, 1990;Qureshi et al, 2003), hydrogen exchange/2D NMR (Jeng et al, 1990), X-ray scattering (Cinelli et al, 2001). Conclusion: It has been observed that pH have affected ditrisbution of secondary structures.…”
Section: Resultssupporting
confidence: 92%
“…For proteins unfolded by various denaturants or elevated temperatures, many studies have demonstrated that SAXS can be an effective tool to probe the global structure and the structure evolution even on a sub-millisecond scale (Chen et al, 1996;Segel et al, 1999;Doniach, 2001;Uzawa et al, 2004). Of the many SAXS studies on proteins structures, the majority seems to focus on the global size and the change in size of proteins in different solution conditions, with the local chain behavior discussed qualitatively using a Kratky-Porod plot and/or the pair distribution function p(r) (Cinelli et al, 2001). The size of the protein studied is often referred to the radius of gyration R g extracted from the corresponding SAXS data in the lowangle scattering region using the Guinier approximation.…”
Section: Introductionmentioning
confidence: 99%
“…We have further utilized SAS to investigate tranglutaminase thermal unfolding because the loss of protein native structure is usually reflected by an increase in the gyration radius (Cinelli et al 2001;Millet et al 2002). This occurs also in the case of denaturation of transglutaminase submitted to step-wise increase in temperature up to 70°C.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%